Electronic Publishing -- a Journal and its Production - Brailsford, David F.; Beach, Richard (Cambridge University Press, 1989)
The use of the term "Electronic Publishing" transcends any notions of the paperless office and of a purely electronic transfer and dissemination of information over networks. It now encompasses all computer-assisted methods for the production of documents and includes the imaging of a document on paper as one of the options to be provided by an integrated processing scheme. Electronic publishing draws heavily on techniques from computer science and information technology but technical, legal, financial and organisational problems have to be overcome before it can replace traditional publication mechanisms. These problems are illustrated with reference to the publication arrangements for the journal `Electronic Publishing Origination, Dissemination and Design'. The authors of this paper are the co-editors of this journal, which appears in traditional form and relies on a wide variety of support from electronic technologies in the pre-publication phase.